Financial Management Information System Website for Contributions in Taman Kradenan Asri Cluster Area - Namudani, Ninggar; Nugroho, Agus Cahyo; Widiantoro, Albertus Dwiyoga (Journal of Business and Technology, 2024)
A social contribution payment system in a housing estate is usually applied for specific purposes. At Taman Kradenan Asri Cluster Area several fees are imposed. The system used today is still conventionally applied, where the person assigned to collect the contribution bill records when payment is made in a book. Because there are several fees, several books are needed and adjusted to the type of contribution. This system requires more workforce and costs and allows human error to occur. Besides, residents cannot access it to check their bills. Therefore, research was carried out with the title "Financial Management Information System Website for Contributions in Taman Kradenan Asri Cluster Area" to solve the solution to the problem above. In its creation, this web page applies the CRUD concept (Create, Read, Update, and Delete) and connects to a MySQL database which is used to store data in real time. This system has an admin and citizen side, where the admin side can carry out the process of adding, updating, and deleting contribution billing data. Meanwhile, on the citizen side, they can see data on paid contributions and make an appointment to collect contributions. Testing of this system was carried out by conducting interviews with related parties and the results of these interviews showed that the system designed could facilitate the process of recording and checking contribution bills from the side of officers and residents.